Phaleria macrocarpa Leaves Extract Reduce Tumors Growth and Improve Histological Changes of Liver and Kidney on 4T1 Breast Cancer Mice Model - Aminullah, Lela -; Christina, Yuyun Ika; Rifa'i, Muhaimin -; Djati, Muhammad Sasmito (The Journal of Experimental Life Science, 2022)
Breast cancer is a type of cancer that highly occurs globally and causes death cases. Of the many ways of treating breast cancer, chemotherapy is the most recommended, even though it causes various disturbing side effects. Therefore, alternative medicine using bioactive compounds of medicinal plants has begun to be widely used, for example, Phaleria macrocarpa, a plant native to Indonesia with anticancer and antioxidant activity. The liver and kidneys are important organs that function to maintain body homeostasis. The use of crude extracts of medicinal plants often causes damage to those organs at inappropriate doses. This research aimed to get an effective dose for reducing breast cancer growth and is safe for the liver and kidneys. A total of 36 mice were divided into six groups, including healthy control, cancer control, cisplatin, and three doses of P. macrocarpa extract (58.9, 117.8, and 235.6 mg.kg-1). The experimental animals were injected using a 4T1 cell line and treated orally using P. macrocarpa leaf ethanol extract for two and three weeks. The tumor volume of mice was measured periodically. At the end of treatment, mice were sacrificed, and their liver and kidney organs were isolated. Both organs were then prepared for H&E staining and observed using a microscope. The results showed that a dose of 58.9 mg.kg-1 and 117.8 mg.kg-1 of P. macrocarpa extract could reduce tumor volume by more than 90%, and the 117.8 mg.kg-1 dose is the safest dose to use because it does not affect the kidney and cause chronic damage to liver tissue. Keywords: extract, kidney, liver, tissue damage, tumor.